2020
DOI: 10.1002/ange.202000555
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Pressure‐Induced Emission Modulation with Linker Rotation in a Photoluminescent MOF

Abstract: Conformational changes of linker units in metalorganic frameworks (MOFs) are often responsible for gateopening phenomena in selective gas adsorption and stimuliresponsive optical and electrical sensing behaviour. Herein, we show that pressure-induced bathochromic shifts in both fluorescence emission and UV/Vis absorption spectra of a two-fold interpenetrated Hf MOF, linked by 1,4-phenylenebis(4-ethynylbenzoate) ligands (Hf-peb), are induced by rotation of the central phenyl ring of the linker, from a coplanar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Thus, more and more scientists have devoted themselves into the research of it in recent years. [82][83][84][85][86][87][88][89][90][91] Especially, Ruren Xu and coworkers proposed "Towards a new discipline of condensed matter chemistry" in 2018. [82,83] It is believed that after constant exploration, the molecular structure-packing property relationship could be revealed clearly and the adjustment of luminescence property in aggregation state could be easily realized from the source of molecular design.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Thus, more and more scientists have devoted themselves into the research of it in recent years. [82][83][84][85][86][87][88][89][90][91] Especially, Ruren Xu and coworkers proposed "Towards a new discipline of condensed matter chemistry" in 2018. [82,83] It is believed that after constant exploration, the molecular structure-packing property relationship could be revealed clearly and the adjustment of luminescence property in aggregation state could be easily realized from the source of molecular design.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…15,16 Phase transition has been reported to be an effective approach to tune the property of flexible MOFs, 17 and this can be triggered by ligand substitution, 18 guest uptake, 19 or by changes in temperature 20 and/or pressure. 21 However, studies on the impact of single-crystal-to-singlecrystal (SCSC) transformations on proton conductivity in MOFs have been reported rarely. 22,23 We report herein the SCSC transformation via ligand substitution in a nonporous Pb(II)-based MOF, MFM-722(Pb)-DMA, and the enhancement of proton conductivity in the resultant MFM-722(Pb)-H 2 O.…”
mentioning
confidence: 99%
“…One area where the use of pressure has seen a significant rise in popularity is in the study of functional materials where high-pressure diffraction studies performed in conjunction with other high-pressure measurements on the same sample have helped develop structure-property relationships. Supplementary techniques have included high-pressure UV-Vis [10], fluorescence emission [11], conductivity [12], Mossbauer [13] and magnetic measurements. These combined studies have revealed how structural distortions, caused by increasing pressure, have enforced changes in the physical properties of materials.…”
Section: Introductionmentioning
confidence: 99%
“…These combined studies have revealed how structural distortions, caused by increasing pressure, have enforced changes in the physical properties of materials. Examples include measuring changes in conductivity and band structure in molecular conductors [12], monitoring framework 'breathing effects' on uptake of guest species within porous Metal-Organic Framework materials [14], and how structural changes in encapsulated fluorophores affect emission properties [11]. One area where this approach has made a significant impact is in the field of magnetism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation